Prospects for the Development of Decorative Nursery in the Crimea - REPETSKAYA, Anna Igorevna; SAVUSHKINA, Irina Gennadievna; GORODNYAYA, Ekaterina Vasilievna; KRAVCHUK, Elena Alexandrovna; VISHNEVSKY, Stanislav Olegovich; NEVKRYTAYA, Natalya Vladimirovna; SALOGUB, Roman Vasilievich (Journal of Environmental Management and Tourism, 2020)
Potential volume of planting material market for ornamental crops was calculated based on the analysis of master plans for the development of Crimean cities taking into account standards for planting trees and shrubs. Data were obtained on territorial belonging, purpose, production cycle, and range of peninsula nurseries. It was proposed to use plus trees growing in urban conditions as mother trees for production of planting material adapted to the urban ecological and climatic conditions of this area. We have previously proposed a basic recommended assortment to green the Piedmont zone of Crimea. On its basis a GIS of plus trees of large landscape objects of Simferopol was developed.